The message of the Jerusalem Council in the Acts of the Apostles a linguistic stylistic analysis - Dawson, Zachary K. (Boston BRILL, 2022)
Intro -- Contents -- Acknowledgements -- List of Figures and Tables -- List of Abbreviations -- 1 The Relationship between Purpose and Parallelism in Acts: A Literature Review -- 1 Introduction -- 2 A History of Proposals on the Purpose and Parallelisms of Acts -- 2.1 Nineteenth-Century Scholarship -- 2.2 Twentieth-Century Scholarship -- 2.3 Twenty-First Century Scholarship -- 3 Conclusion -- 2 Linguistic Stylistics: Theory, Model, and Methodology -- 1 Introduction -- 2 Stylistics: Theory and Main Concepts -- 3 Social Semiotic Stylistics -- 4 Supplementary Principles for Stylistic Analysis -- 5 A Model and Method for Linguistic Stylistic Analysis -- 5.1 Experiential Meaning and the System of Transitivity -- 5.2 Logical Meaning, the Clause Complex, and the Systems of Taxis and Logico-Semantics -- 5.3 Textual Meaning, Markedness, Prominence, and Foregrounding -- 5.4 Interpersonal Meaning, Intertextuality, and Intertextual Thematic Analysis -- 6 Conclusion -- 3 The Story of Cornelius and Peter: A Transitivity Analysis of Acts 10:1-11:18 -- 1 Introduction -- 2 The First Account of Cornelius's Vision (10:1-8) -- 2.1 Transitivity Structure -- 2.2 Assessment -- 3 The First Account of Peter's Vision (10:9-16) -- 3.1 Transitivity Structure -- 3.2 Assessment -- 4 Peter Meets Cornelius's Men (10:17-23a) -- 4.1 Transitivity Structure -- 4.2 Assessment -- 5 Peter Meets Cornelius (10:23b-33) -- 5.1 Transitivity Structure -- 5.2 Assessment -- 6 Peter's Speech (10:34-43) -- 6.1 Transitivity Structure -- 6.2 Assessment -- 7 The Holy Spirit's Descent (10:44-48) -- 7.1 Transitivity Structure -- 7.2 Assessment -- 8 Peter's Report to the Jerusalem Church (11:1-18) -- 8.1 Transitivity Structure -- 8.2 Assessment -- 9 Summary and Conclusion -- 4 Peter's Vision and 1 Enoch's Book of Dreams: An Intertextual Thematic Analysis of Acts 10:1-11:18 -- 1 Introduction.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift